Design and thermal performance investigation of a box cooker with flexible solar collector tubes: An experimental research. (1st September 2020) - Saxena, Abhishek; Cuce, Erdem; Tiwari, G.N.; Kumar, Avnish
Abstract: In recent years, solar cookers have been technologically promoted by most of the national governments as renewable and sustainable cooking system round the globe. In the present article, a solar box cooker (SBC) has been developed for fast response and uninterrupted cooking process. For this purpose, a cylindrical copper tube infused with thermal energy storage (TES) has been designed and tested under a modified SBC. Experimental study has been carried out on three different TES materials such as; grainy carbon powder, paraffin wax and specific mixture of carbon powder and paraffin. Specifically, twelve TES filled tubes have been brought into the use for experimentation at three different configurations. Results indicate that the modified cooker has better performance in terms of efficiency (53.81%), overall heat loss coefficient (5.11 W/m 2 °C), cooking power (68.81 W) and heat transfer coefficient (56.78 W/m 2 °C) in comparison with a conventional SBC and other designs using different TES materials. PCM infused tubes are low in cost and flexible to carry with SBC for outdoor cooking. It can easily be carried anywhere along with cooker. This novel configuration enables a fast response cooking with an enhanced efficiency irrespective of climatic conditions. The total cost of SBC is estimated about 39.11. Highlights: Cylindrical tubes of copper has designed to carry high capacity energy storage material. Thermal efficiency of hot box cooker has improved by 53.81%. Cooking power of hot box cooker has improved by 68.81 W. Total cost of the modified cooker is only 39.11 USD. Modified cooker is feasible to perform at low ambient conditions round the year.